BORIS: a free, versatile open‐source event‐logging software for video/audio coding and live observations - Friard, Olivier; Gamba, Marco; Fitzjohn, Richard (Methods in ecology and evolution, 2016)
Summary Quantitative aspects of the study of animal and human behaviour are increasingly relevant to test hypotheses and find empirical support for them. At the same time, photo and video cameras can store a large number of video recordings and are often used to monitor the subjects remotely. Researchers frequently face the need to code considerable quantities of video recordings with relatively flexible software, often constrained by species‐specific options or exact settings. BORIS is a free, open‐source and multiplatform standalone program that allows a user‐specific coding environment to be set for a computer‐based review of previously recorded videos or live observations. Being open to user‐specific settings, the program allows a project‐based ethogram to be defined that can then be shared with collaborators, or can be imported or modified. Projects created in BORIS can include a list of observations, and each observation may include one or two videos (e.g. simultaneous screening of visual stimuli and the subject being tested; recordings from different sides of an aquarium). Once the user has set an ethogram, including state or point events or both, coding can be performed using previously assigned keys on the computer keyboard. BORIS allows definition of an unlimited number of events (states/point events) and subjects. Once the coding process is completed, the program can extract a time‐budget or single or grouped observations automatically and present an at‐a‐glance summary of the main behavioural features. The observation data and time‐budget analysis can be exported in many common formats (TSV, CSV, ODF, XLS, SQL and JSON). The observed events can be plotted and exported in various graphic formats (SVG, PNG, JPG, TIFF, EPS and PDF).